Driving chronicity in rheumatoid arthritis: perpetuating role of myeloid cells. (2nd February 2018) - Alivernini, S; Tolusso, B; Ferraccioli, G; Gremese, E; Kurowska-Stolarska, M; McInnes, I B
Summary: Acute inflammation is a complex and tightly regulated homeostatic process that includes leucocyte migration from the vasculature into tissues to eliminate the pathogen/injury, followed by a pro-resolving response promoting tissue repair. However, if inflammation is uncontrolled as in chronic diseases such as rheumatoid arthritis (RA), it leads to tissue damage and disability. Synovial tissue inflammation in RA patients is maintained by sustained activation of multiple inflammatory positive-feedback regulatory pathways in a variety of cells, including myeloid cells. In this review, we will highlight recent evidence uncovering biological mechanisms contributing to the aberrant activation of myeloid cells that contributes to perpetuation of inflammation in RA, and discuss emerging data on anti-inflammatory mediators contributing to sustained remission that may inform a novel category of therapeutic targets. Graphical Abstract: